Antioxidant and Cytotoxicity Profile of the Selected Alcoholic Beverages Widely Consumed in the Maharashtra State of India (Indian Journal of Public Health Research & Development, 2020)
The health concern of the alcoholic beverages has remained a key issue to be addressed to the consumers.The aim of the present study was to assess the antioxidant activity and cytotoxicity of the selected 22bottled commercial alcoholic brands widely consumed in the Maharashtra state of India. The result of thepresent study shows that the brands of wines followed by whiskies and rums were more effective as freeradical scavenging agents, containing considerable amount of polyphenols. Overall, the vodaka brandswere observed to be more cytotoxic as compared to other brands. With few exceptions, there exists apositive correlation in the amount of polyphenols and free radical scavenging activity, while the former wasnegatively correlated with cytotoxicity.
Keywords: Antioxidant; Alcoholic Beverages; Cytotoxicity; Polyphenol